Impacts of parental technoference on parent-child relationships and child health and developmental outcomes: a scoping review protocol - Lyndsay Jerusha Mackay; Jelena Komanchuk; K. Alix Hayden; Nicole Letourneau (Systematic Reviews, 2022)
Abstract Background With increases in the use of technological devices worldwide, parental technoference is a potential threat to the quality of parent-child relationships and children’s health and development. Parental technoference refers to disrupted interactions between a parent and child due to a parent’s use of a technological device. The aims of this scoping review are to map, describe, and summarize the existing evidence from published research studies on the impacts of parental technoference on parent-child relationships and children’s health and development and to identify the limitations in the studies and gaps in the literature. Methods This scoping review will be conducted in accordance with the Joanna Briggs Institute (JBI) methodology. A search for relevant research studies will be undertaken in APA PsycInfo, MEDLINE, Central, Cochrane Database for Systematic Reviews, JBI EBP, and Embase (OVID). CINAHL (Ebsco) and Scopus will also be searched. Grey and popular literature will be excluded. This review will include primary research studies and review papers published in English with no time limit that identify the impacts of technoference on parent-child relationships and child health and developmental outcomes. Parent participants include primary caregivers, either biological, adopted, or foster parents, of children under the age of 18 who engage in technoference. Two reviewers will independently screen the titles, abstracts, and full texts of studies according to the inclusion and exclusion criteria. Disagreements will be resolved through discussion with a third researcher. Data will be extracted into a data charting table including author(s), year of publication, country, research aim, methodology/design, population and sample size, variables/concepts, and corresponding measures and main results. Data will be presented in tables and figures accompanied by a narrative summary. Discussion The goal of this scoping review is to present an overview of the evidence on the impacts of parental technoference on parent-child relationships and child and health developmental outcomes, highlighting the current risk of children of today. It will identify gaps in the literature, inform future research, advise recommendations for parents on technological device use, and possibly guide the development of interventions aimed at addressing parental technoference. Trial registration Open Science Framework https://doi.org/10.17605/OSF.IO/QNTS5